1994
DOI: 10.3109/10428199409049695
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia, Parathyroid Hormone-Related Protein Expression and Human T-cell Leukemia Virus Infection

Abstract: Adult T-cell leukemia (ATL) associated with HTLV-1 infection is characterized by the development of hypercalcemia in over two thirds of patients. Dysregulation of cellular gene transcription by viral proteins is an emerging paradigm for molecular pathogenesis of disease. A recent example is the parathyroid hormone-related protein (PTHrP) gene, which has been implicated in the hypercalcemia of ATL, and is transactivated by the HTLV-1 tax and HTLV-11 tax proteins. PTHrP is expressed at high levels in leukemia ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…With an unusually high association of hypercalcemia, about 40% of patients with ATL are known to eventually develop hypercalcemia (15,16). On the other hand, breast carcinoma was relatively uncommon in our series as well as in other Asian studies (9,10), in contrast to Western series with this carcinoma typically accounting for more than 20% (3,6,(17)(18)(19).…”
Section: The Major Causes Of Hypercalcemia Were Found To Be Malignanccontrasting
confidence: 48%
“…With an unusually high association of hypercalcemia, about 40% of patients with ATL are known to eventually develop hypercalcemia (15,16). On the other hand, breast carcinoma was relatively uncommon in our series as well as in other Asian studies (9,10), in contrast to Western series with this carcinoma typically accounting for more than 20% (3,6,(17)(18)(19).…”
Section: The Major Causes Of Hypercalcemia Were Found To Be Malignanccontrasting
confidence: 48%
“…During the multi-stage carcinogenesis of ATLL, T-cell transformation, proliferation and progression require the effects of humoral and local factors. In previous studies, we and others have shown that both PTHrP and MIP-1α are important for HHM development in ATLL [3,4,7,8,48,49]. Interestingly, we also found that both factors were expressed in the early stages of ex vivo T-cell transformation and immortalization [13].…”
Section: Discussionsupporting
confidence: 53%
“…1). Eighty percent of ATLL patients develop humoral hypercalcemia of malignancy (HHM), a severe complication resulting from increased osteoclastic bone resorption and renal calcium reabsorption (2). HHM in ATLL patients leads to a mean survival of <1 year (3); therefore, it is urgent to develop new therapies to sufficiently reduce HHM and eliminate tumor progression in ATLL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PTHrP plays a major role in the pathogenesis of HHM (10); however, recent studies have suggested that cytokines and chemokines, such as MIP-1a, a chemoattractant and activator of monocytes during inflammation, can induce osteoclastic bone resorption and serve as a potential survival and osteoclast stimulatory factor in cancer (11). Increased concentrations of plasma PTHrP and MIP-1a are reliable clinical biomarkers of hypercalcemia in ATLL and represent potential therapeutic targets (2,9).…”
Section: Introductionmentioning
confidence: 99%